Hierarchical control of a direct current microgrid with energy storage systems in a distributed topology : : doctoral thesis - Dragičević, Tomislav (T. Dragičević ; Fakultet elektrotehnike i računarstva, 2013)
SUMMARY: A Microgrid (MG) is a standalone or grid-connected hybrid renewable system that uses distributed renewable and non-renewable energy sources and energy storage systems (ESSs) to supply power to local loads. The aim of this thesis is developement of its higher control level. It has to deal with RESs, which are controllable only within the limits imposed by natural phenomenon, while the battery recharging usually has to be done in a specific way. Moreover, the technical constraints such as stability margins and maintenance of acceptable voltage deviation within the system must also be respected while considering the aforementioned issues. Also, a battery management system (BMS) based on extended Kalman filter has been constructed and tested through simulations and experiments. Then, hardware in the loop model of the battery has been used in development stage of two coordination strategy methods for dc MG. First was assembled in a centralized way, while the other one utilized a distributed coordination concept bad on power-line signalling (PLS). -